An Islamic Legal Analysis of the Determination of the Mandatory Inheritance Share for a Common-Law Wife When the Deceased Has a Legitimate Wife (A Study of the Muara Bulian Religious Court Decision Number 183/Pdt.G/2023/PA.Mbl) - Habibi Abdul Jalil; Mohammad Jamin; Solikhah (Siber International Journal of Advanced Law (SIJAL), 2026)
This study analyzes the validity of mandatory wills for unregistered wives based on Decision Number 183/Pdt.G/2023/PA.Mbl. The background of this study is the existence of inheritance conflicts due to the practice of unregistered marriages that are not registered with the state, which creates uncertainty about inheritance rights for the parties concerned. This study aims to determine the validity of the legal status of mandatory wills for unregistered wives according to Islamic law and Indonesian legislation. This study uses normative legal methods with a statutory and conceptual approach. The results of the study concluded that under positive law and Supreme Court Circular Letter Number 2 of 2019, unregistered wives do not have inheritance rights because their marriages are not registered. However, the judge made a legal breakthrough by granting mandatory wills (a maximum of one-third of the assets) to unregistered wives for the sake of justice for their services in caring for the heir. The implication is that although mandatory wills provide protection for unregistered wives, this policy has the potential to cause economic injustice for legal wives and weaken the legal order of marriage registration and the prevention of unregistered polygamy.